Mangiferin Against Respiratory Diseases: Pharmacological Targets and Prospects - Kazi Ahsan Ahmed; Nusrat Afrin; Popy Ghosh; Irin Amin Heya; Sajidur Rahman Akash; Akhi Moni; Mohammad Nazrul Islam; Md. Golzar Hossain; Alessandra Sinopoli; Md Abdul Hannan; Md Jamal Uddin (Pharmacology Research & Perspectives)
ABSTRACT Respiratory diseases are associated with high mortality worldwide. Respiratory infections can lead to the emergence of chronic respiratory diseases. Scientists are constantly striving to identify new therapies with reduced side effects. The rise of antibiotic resistance and the scarcity of effective treatments further necessitate the development of novel therapeutics specific to respiratory diseases. Extensive research has been conducted on natural products that could be effective against respiratory diseases. Mangiferin, a polyphenol with a C‐glycosyl xanthone structure, is a bioactive phytochemical that has potential applications in the treatment of respiratory tract infections. Mangiferin could be a therapeutic option against respiratory diseases because of its ability to target a variety of pharmacological pathways implicated in the development of these infections. It has been shown to limit infections, lower inflammation, control immune responses, and enhance host defense mechanisms. This review provides comprehensive insight into mangiferin's potential against various respiratory disorders, focusing on its pharmacological activity and therapeutic prospects. Despite the potential of mangiferin against respiratory problems‐related pathobiology, additional scientific validation through clinical trials is required before the clinical application of mangiferin in the management of respiratory diseases.